2016
DOI: 10.1109/tmi.2016.2559499
|View full text |Cite
|
Sign up to set email alerts
|

Radiolucent 4D Ultrasound Imaging: System Design and Application to Radiotherapy Guidance

Abstract: Four-dimensional (4D) ultrasound (US) is an attractive modality for image guidance due to its real-time, non-ionizing, volumetric imaging capability with high soft tissue contrast. However, existing 4D US imaging systems contain large volumes of metal which interfere with diagnostic and therapeutic ionizing radiation in procedures such as CT imaging and radiation therapy. This study aimed to design and characterize a novel 4D Radiolucent Remotely-Actuated UltraSound Scanning (RRUSS) device that overcomes this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…The waterequivalent material employed in radiolucent probes should therefore produce similar results to those obtained in this study, however, have obvious advantages if left in place during planning CT imaging. 37 Small differences in the shape of the kV and MV dose perturbations were visible (see Fig. 6).…”
Section: Discussionmentioning
confidence: 92%
“…The waterequivalent material employed in radiolucent probes should therefore produce similar results to those obtained in this study, however, have obvious advantages if left in place during planning CT imaging. 37 Small differences in the shape of the kV and MV dose perturbations were visible (see Fig. 6).…”
Section: Discussionmentioning
confidence: 92%
“…While an array allows for 3D reconstruction of the dose distribution, the placement of transducers in such a geometry may be difficult due to radiation beam interference. However, it could be possible to account for transducers during the treatment planning stage, and a recent study demonstrated the construction and operation of a radiolucent transducer . Using a single transducer limits the amount of dosimetric information that can be extracted from detected acoustic signals, however, clinical implementation may become easier.…”
Section: Linac Photon Beam Dosimetrymentioning
confidence: 99%
“…Second, the radiation can be delivered through the probe, but it requires that the possible dose deviations are taken into account during the treatment planning process, as investigated by, for example, Bazalova-Carter et al [ 76 ]. As a third solution, Schlosser and Hristov [ 77 ] designed a 4D radiolucent US probe with significantly less metal components close to the imaging field. This probe should produce a minimal interference with the radiation beam.…”
Section: Challengesmentioning
confidence: 99%